Pendekatan Keamanan Manusia dalam Studi Perbatasan Negara - Sudiar, Sonny (Jurnal Hubungan Internasional, 2018)
The study of state border have always been an interesting topic of discussion among the IR’s scholars, this is because the border issues are related to territorial issues and state sovereignty. So that discussions about state borders are always dominated by traditional security approaches that put the ecountry as the primary actor.While this article seeks to use the human security approach in reviewing state border issues. This is done as a form of response to the dynamics of change in international relations. Unlike traditional security approaches that always put the state as the object of reference, the human security approach places the individual as the object of reference. Human security is an approach that is focus on individual security. According to UNDP there are seven universal components in human security approach; economic security, food security, health security, environment security, personal security, community security and political security.